Economic effects of a nuclear-phase out policy: A CGE analysis - Lucas Bretschger; Roger Ramer; Lin Zhang (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
The paper investigates the long-run consequences of a phase-out of nuclear energy for the Swiss economy. We apply the CITE model, a CGE model with fully endogenous growth, and complement it with a bottom-up model. We find that the nuclear phase-out can be achieved at relatively low costs, even when the expansion capacities of other technologies are limited. Consumer welfare decreases by 0.4% at the maximum compared to business as usual. Our results show that an economy can cope well with ambitious energy policies through sufficient innovation. Economic growth is not slowed down significantly. The phase-out policy contributes to a structural shift in favor of innovative, energy extensive sectors. It does not work against the climate policy goals but rather accelerates the transition to a less energy-dependent economy.
Keywords: Q43; C68; Q48; O41; 330; Energy and growth; nuclear phase out; CGE model; induced innovation; Kernenergie; Energiepolitik; Wirkungsanalyse; Wirtschaftswachstum; Allgemeines Gleichgewicht; Simulation; Endogenes Wachstumsmodell; Theorie